2016
DOI: 10.3390/rs8080655
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Downscaling Algorithm for Satellite-Based Precipitation over the Tibetan Plateau Based on NDVI, DEM, and Land Surface Temperature

Abstract: Abstract:Precipitation is an important controlling parameter for land surface processes, and is crucial to ecological, environmental, and hydrological modeling. In this study, we propose a spatial downscaling approach based on precipitation-land surface characteristics. Land surface temperature features were introduced as new variables in addition to the Normalized Difference Vegetation Index (NDVI) and Digital Elevation Model (DEM) to improve the spatial downscaling algorithm. Two machine learning algorithms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 41 publications
6
80
0
3
Order By: Relevance
“…Regarding machine learning procedures, [27] reported that post-calibration of the downscaled TRMM images reduces RMSE and bias, which is also consistent with the results obtained in this study. Finally, [28] also reported improvements over TRMM using machine learning techniques. However, accuracy was decreased after applying residual correction using TRMM at the original resolution as the dependent variable and spline interpolation.…”
Section: Results Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding machine learning procedures, [27] reported that post-calibration of the downscaled TRMM images reduces RMSE and bias, which is also consistent with the results obtained in this study. Finally, [28] also reported improvements over TRMM using machine learning techniques. However, accuracy was decreased after applying residual correction using TRMM at the original resolution as the dependent variable and spline interpolation.…”
Section: Results Summary and Discussionmentioning
confidence: 99%
“…The same independent variables were applied in [26] for annual precipitation in mainland China, where the Random Forest regression furnished promising results for large areas, outperforming the multiple linear regression and exponential models. This machine learning approach was further developed in [27,28] for the Tibetan Plateau. The former applied post-calibration using ground measurements, while the latter incorporated land surface temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, spatial downscaling to increase spatial resolution [12] is essential when using coarse spatial resolution satellite-derived precipitation data for local-scale analysis in areas where rain gauges are very sparse. Several statistical/geostatistical methods have been proposed for spatial downscaling, some of which integrate auxiliary environmental variables, such as elevation and vegetation index, at a fine spatial resolution via regression analysis and residual correction [4,[13][14][15][16][17][18][19][20]. Promising downscaling results have been obtained by previous studies, but the predictive performance of any downscaling method is subject to the accuracy of input satellite precipitation product.…”
Section: Introductionmentioning
confidence: 87%
“…For example, multiple linear regression (MLR), exponential models, geographically weighted regression (GWR), random forests and support vector machines have been applied for downscaling satellite-based precipitation products (Immerzeel et al, 2009;Chen et al, 2014;Chen et al, 2015;Jing et al, 2016). When estimating the trend components using regression models, the different regression models are affected by the quality of input coarse resolution satellite-based products.…”
Section: Introductionmentioning
confidence: 99%